1996
DOI: 10.1007/bf00231925
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of ethylene inhibitors and putrescine on shoot regeneration from hypocotyl explants of Chinese radish (Raphanus sativus L. var. longipinnatus Bailey) in vitro

Abstract: The role of ethylene and putrescine on shoot regeneration from hypocotyl explants of Chinese radish (Raphanus sativus L. var. longipinnatus Bailey cv. Red Coat) was investigated. Explants were recalcitrant in culture, but exogenous application of ethylene inhibitor [20-30 μM aminoethoxyvinylglycine (AVG) or AgNO3] enhanced shoot regeneration of explants grown on medium supplemented with 2 mg/l N(6)-benzyladenine and 1 mg/l 1-naphthaleneacetic acid. The best regeneration occurred in the medium containing AgNO3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…SN has been used in several studies in a range of concentrations from 0 to 100 µM (Pua et al 1996), and its addition to culture media has resulted in contradictory effects depending on the plant materials and experimental conditions (Biddington 1992;Moshkov et al 2008). In our study, a reduction in B of about 20% was observed in S. pennellii explants cultured on medium with SN concentrations higher than 14.5µM (Table 1).…”
Section: Effect On Organogenesis Of Different Doses Of Ethylene Inhibmentioning
confidence: 99%
“…SN has been used in several studies in a range of concentrations from 0 to 100 µM (Pua et al 1996), and its addition to culture media has resulted in contradictory effects depending on the plant materials and experimental conditions (Biddington 1992;Moshkov et al 2008). In our study, a reduction in B of about 20% was observed in S. pennellii explants cultured on medium with SN concentrations higher than 14.5µM (Table 1).…”
Section: Effect On Organogenesis Of Different Doses Of Ethylene Inhibmentioning
confidence: 99%
“…Methylglyoxal-bis-(guanylhydrazone) (MGBG), an inhibitor of spermidine biosynthesis, was reported to increase the regeneration frequencies from 7% to 63% in Brassica and other genera (Sethi et al 1990). In contrast, putrescine, a polyamine, was found to enhance shoot regeneration in Chinese radish when used with silver nitrate or aminoethoxyvinylglycine (Pua et al 1996). On the other hand, putrescine was not effective when used alone, but was synergistic with ethylene inhibitors.…”
Section: Age and Size Of The Explantsmentioning
confidence: 87%
“…In Chinese radish (Raphanus sativus var. longipinnatus), the combination of silver nitrate and aminoethoxyvinylglycine was found to enhance shoot regeneration significantly (Pua et al 1996). Other ethylene inhibitors, which can be used in combination or as an alternative, include silver thiosulphate (Eapen and George 1997) and aminoethoxyvinylglycine used by Chi (1990) for B. rapa and B. juncea, Chi (1993) for B. juncea, andBurnett (1994) for B. rapa.…”
Section: Hyperhydricity and Tissue Necrosismentioning
confidence: 99%
“…oleifera (Burnett et al 1994), Brassica campestris ssp. pekinensis (Chi et al 1991;Zhang et al 1998), hypocotyls of Brassica juncea (Pua and Chi 1993) and Raphanus sativus (Pua et al 1996), peduncle and leaf segments of Brassica napus (Eapen and George 1997;Akasaka-Kennedy et al 2005). AgNO 3 is a potent inhibitor of ethylene action, and ethylene is considered to suppress shoot morphogenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%